Can human extinction be morally desirable? A critique of David Benatar’s anti-natalism - van Niekerk , Anton (Stellenbosch Theological Journal, 2022)
According to David Benatar’s anti-natalism, the extinction of all sentient life, including that of humans, is morally desirable. That claim is contested in this article. The author commences by showing parallels between Benatar’s position and that of the existentialist Albert Camus. He points out that, also for Camus, the claim that "death is better" is meant in a moral sense. This is followed by a general exposition of Benatar’s anti-natalism. Particular attention is paid to Benatar’s argument about the "symmetry of pleasure and pain": the presence of pain is bad, whereas the presence of pleasure is good. However, whereas the absence of pain is good, it cannot necessarily be argued that the absence of pleasure is bad; what can, at most be claimed, is that the absence of pleasure is not bad. The author develops three arguments against Benatar’s position. He firstly (drawing on Dawkins) points out that Benatar’s position contests the most primordial of all instincts that characterize the phenomenon of life, i.e. reproduction. Secondly, drawing on Irenaeus and Hick, the author argues that the idea of a painless sentient existence is untenable. Thirdly, as suggested by the article’s title, the author argues that it does not make sense to promote a moral argument for the desirability of the non-existence of human life, since such an argument presupposes, for its very validity, due recognition as a moral argument or claim in an environment of morally responsible human interactions – that which Benatar’s argument suggests should disappear completely in the universe that he proposes.